2014
DOI: 10.3382/ps.2013-03810
|View full text |Cite
|
Sign up to set email alerts
|

The effect of nutritional status on myogenic gene expression of satellite cells derived from different muscle types

Abstract: Satellite cells (SC) are a multipotential stem cell population responsible for facilitating posthatch muscle fiber hypertrophy. The proliferation and differentiation of SC is sensitive to nutritional regimen, and the SC response to nutrition varies depending upon their muscle type of origin. The objective of the current study was to determine the effect of altering protein synthesis on the expression of several key genes regulating SC activity and the effect of muscle type. Satellite cells isolated from the fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 74 publications
3
9
0
1
Order By: Relevance
“…28 Second, much of protein synthesis for cell viability requires enough nutrition, lack of nutrition could block this process. 29,30 Our previous study also revealed that the expression of HIF-1 and VEGF and TGF-b1 reduced in regressive scar tissue, which is in accordance with this in vitro study. 6,20 From the data reported herein, it appears that severe hypoxia and malnutrition not only contribute to the inhibition of collagen production, but also reduces HIF-1, TGFb 1 , VEGF expression and cell viability.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…28 Second, much of protein synthesis for cell viability requires enough nutrition, lack of nutrition could block this process. 29,30 Our previous study also revealed that the expression of HIF-1 and VEGF and TGF-b1 reduced in regressive scar tissue, which is in accordance with this in vitro study. 6,20 From the data reported herein, it appears that severe hypoxia and malnutrition not only contribute to the inhibition of collagen production, but also reduces HIF-1, TGFb 1 , VEGF expression and cell viability.…”
Section: Discussionsupporting
confidence: 89%
“…First, it has been revealed that the activation of HIF‐1 could stabilize p53 by cross‐talk with HIF‐1, P53 accumulation could inversely repress HIF‐1 activity by competing to bind with p300, and destabilizes HIF‐1α and reduces its expression, eventually contribute to p53‐mediated cell apoptosis . Second, much of protein synthesis for cell viability requires enough nutrition, lack of nutrition could block this process . Our previous study also revealed that the expression of HIF‐1 and VEGF and TGF‐β1 reduced in regressive scar tissue, which is in accordance with this in vitro study …”
Section: Discussionsupporting
confidence: 68%
“…This result is probably due to the low transcriptional activity in quiescent satellite cells, making a quantitative comparison complicated, but it is consistent with the results of other studies performed on mouse adult satellite cells (Beauchamp et al, 2000;Tajbakhsh and Buckingham, 2000;Crist et al, 2012). The proliferative ability and temporal expression of mRNA by satellite cells seems to be dependent on the host and the muscle from which they are collected (Powell et al, 2014). Additional levels of heterogeneity are known to exist between satellite cells populations, as well as different extracellular matrix protein compositions, growth kinetics, myoblast fusion capacities, transcription factor profiles, motility kinetics and migratory properties (Biressi and Rando, 2010;Boldrin et al, 2010;Li et al, 2011;Li and Johnson, 2013).…”
Section: Discussionsupporting
confidence: 89%
“…However, in low-serum media, p. major satellite cells differentiated more quickly into myofibers than b. femoris cells . In response to nutritional restriction, chicken p. major and b. femoris satellite cells differentially express myogenic regulatory factors (Powell et al 2014b) and p. major satellite cells had a higher adipogenic potential than b. femoris satellite cells (Powell et al 2014a). Comparisons of the p. major and b. femoris satellite cells in the current study demonstrated that p. major satellite cells are much more sensitive to temperature change than b. femoris satellite cells.…”
Section: Discussionmentioning
confidence: 99%